2005
DOI: 10.1104/pp.105.061549
|View full text |Cite
|
Sign up to set email alerts
|

FesM, a Membrane Iron-Sulfur Protein, Is Required for Cyclic Electron Flow around Photosystem I and Photoheterotrophic Growth of the Cyanobacterium Synechococcus sp. PCC 7002

Abstract: While it is known that cyclic electron flow around photosystem I is an important pathway of photosynthetic electron transfer for converting light energy to chemical energy, some components of cyclic electron flow remain to be revealed. Here, we show that fesM, encoding a novel membrane iron-sulfur protein, is essential to cyclic electron flow in the cyanobacterium Synechococcus sp. PCC 7002. The FesM protein is predicted to have a cAMP-binding domain, an NtrC-like domain, a redox sensor motif, and an iron-sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Another feature of Fe-S proteins is that they are often linked to biomembranes (55)(56)(57). Fe-S D-iLDH has been previously identified as a membrane-associated enzyme (34), but no possible transmembrane helix was predicted for the whole Fe-S D-iLDH (http://www.ch.embnet.org/software/TMPRED_form.html).…”
Section: Discussionmentioning
confidence: 99%
“…Another feature of Fe-S proteins is that they are often linked to biomembranes (55)(56)(57). Fe-S D-iLDH has been previously identified as a membrane-associated enzyme (34), but no possible transmembrane helix was predicted for the whole Fe-S D-iLDH (http://www.ch.embnet.org/software/TMPRED_form.html).…”
Section: Discussionmentioning
confidence: 99%
“…Through the analysis of the glucose transporter GlcP and the glucokinase (glk), the accumulation of unmetabolized glucose in the cells caused the growth defect [ 13 ]. Additionally, it has been reported that the loss of FesM, a protein involved in PSI cyclic electron transfer, in Synechococcus sp PCC 7002 prevents mixotrophic growth using glycerol, suggesting that the addition of glycerol affects the reduction state of the PQ pool, leading to poor growth [ 14 ]. In this experiment, the growth of Acaryochloris species was inhibited by the addition of glycerol, sucrose, and glucose, suggesting that the influx of reducing power from these exogenous carbon sources affects the reduction state of the PQ pool, which resulted in inhibited growth ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence emission spectra at 77 K were measured according to Zhao et al [17]. Thylakoid membranes were isolated based on the phase partition method [18] which was modified according Xu et al [19]. Detection of GFP with immunoblotting was performed according Zhao et al [20].…”
Section: Other Methodsmentioning
confidence: 99%